Psychological and organizational impact of bullying over and above negative affectivity: A survey of two nursing contexts. Issue 3 (4th June 2013) - Rodwell, John; Demir, Defne; Steane, Peter
<x xml:space="preserve">Abstract</x> Limited research exists on the impact of bullying across psychological and/or organizationally orientated outcomes for nurses working within different nursing contexts. Research that has explored these outcomes has not considered the potential confounding effects of negative affectivity (NA). This study's aim was to examine the extent hospital and aged care nurses are impacted by bullying on these outcomes, while considering NA. A total of 267 hospital nurses/midwives and 168 aged care nurses from an Australian healthcare organization responded to a survey. The results revealed hospital nurses/midwives who experienced bullying reported higher levels of psychological distress, as well as lower commitment and job satisfaction levels. Aged care nurses who experienced bullying reported lower levels of well‐being and commitment. NA was a significant covariate for most analyses. Thus, nurses across these contexts are affected by bullying in relation to psychological and organizational‐orientated outcomes over and above the effects of NA, particularly for commitment.